Peningkatan Kualitas Pembelajaran melalui Supervisi Akademik di SMA Negeri 13 Pekanbaru - Abdul Gafar (Journal on Education, 2022)
Analysis of School Self-Evaluation and the Results of School Academic Supervision in Pekanbaru 13 Public High School found that the teacher's lack of understanding of the completeness of the administration of learning and the implementation of learning in the classroom was not maximized according to what had been planned, including the use of learning methods and learning media. The population of this study was 27 (twenty seven) teachers who were surveyed as a whole. Data was collected through documentation, observation/observations and interviews. Regarding the increase in competence and quality of teacher learning as seen from the changes during the pre-cycle 6 (six) people in the Very Good category, 17 (seventeen) Good and 4 (four) Enough, to 8 (eight) people in the Very Good category, 15 (five 11) Good, and 2 (two) people Enough in Cycle I, In Cycle II, 11 (eleven) people are in the Very Good category, and 16 (sixteen) are Good. This study found that academic supervision activities can improve teacher competence in preparing learning administration and managing learning activities as well as increasing teachers' ability to use creative, innovative, and fun learning models and media. The suggestion from this research is that the implementation of academic supervision for all teachers can be carried out every semester.